The Effectiveness of Gravity Sketch Application in Virtual Reality for Isometric Drawing - Jaafar, Yusra; Ng, Chuan Huat; Tee, Tze Kiong (Research and Innovation in Technical and Vocational Education and Training, 2024)
In the Grafik Komunikasi Teknikal (GKT), isometric drawing themes are taught utilizing virtual reality (VR) and the Gravity Sketch application. Enhancing pupils’ comprehension of spatial ideas and visualization abilities is the objective. Concerns over the caliber of TVET graduates are raised by the Education Development Plan 2013–2025, which emphasizes the drop in student performance following PMR. During the action research, lesson plans were created and used for isometric drawing themes using virtual reality as a teaching tool. 18 carefully chosen students participated in the action research, which included VR-based learning sessions led by a comprehensive curriculum. Pre-test, pass-test 1, and pass-test 2 data were gathered, and Friedman’s tests showed notable gains. The findings demonstrate that using virtual reality (VR) in isometric sketching enhances student comprehension, satisfaction, and conceptual understanding. In summary, VR successfully enhances comprehension and visualization abilities, indicating broader acceptability in technical education and possible uses in other fields.